Genetic algorithm-enhanced linear quadratic control for balancing bicopter system with non-zero set point - Apriaskar, Esa; Prastiyanto, Dhidik; Utomo, Aryo Baskoro; Manaf, Akhyar Abdillah; Amelia, Ilya; Ilham, Dimas Alfarizky; Bilqis, Viyola Lokahita; Photong, Chonlatee (National Research and Innovation Agency, 2023)
Bicopter is an unmanned aerial vehicle (UAV) with the advantage of saving energy consumption. However, the unique two rotors design presents a challenge in designing a controller that achieves good stability, fast settling time, and the ability to overcome oscillations simultaneously. This article proposes a new control method for bicopter that uses a genetic algorithm optimization approach in the linear quadratic (LQ-GA) control method. The GA is used to search for the best weighting matrix parameters, Q and R, in the Linear Quadratic (LQ) control scheme. The proposed control method was tested on a balancing bicopter test platform with an input in the form of difference in pulse width modulation (PWM) signals for both rotors and an output in the form of roll angle. The control system was evaluated based on the stability of the transient response and the generated control signal. The results of the tests showed that the proposed LQ-GA control method has better stability, faster settling time, and smaller overshoot than the existing PI and standard LQ control methods. Therefore, the proposed LQ-GA control method is the most suitable for use in a balancing bicopter system with a non-zero setpoint.